The influence of communication on theological understanding and cultural formation of theodicy with reference to the Dutch Reformed Church in South Africa - Lombaard, Christoffel Johannes Stephanus (University of Pretoria, 2025)
Dissertation (MTh (Practical Theology))--University of Pretoria, 2024.